The Hellenic Marine Observing, Forecasting and Technology System—An Integrated Infrastructure for Marine Research - Evi Bourma; Leonidas Perivoliotis; George Petihakis; Gerasimos Korres; Constantin Frangoulis; Dionysios Ballas; Vassilis Zervakis; Elina Tragou; Petros Katsafados; Christos Spyrou; Manos Dassenakis; Serafim Poulos; et al. (Journal of Marine Science and Engineering, 2022)
Research infrastructures have been established throughout Europe in order to create robust organizations that will facilitate and enhance research and innovation processes and will advance society with innovative products and services. The Hellenic Integrated Marine Observing, Forecasting and Technology System (component of HIMIOFoTS RI) has been implemented in the framework of the National Roadmap for Research Infrastructures to form a large-scale infrastructure for the marine environment in Greece. It links together ocean observing and forecasting systems, coastal zone monitoring and management practices, as well as ocean engineering testing facilities. The overarching framework of the system supports the coordination of five organizations with expertise in the field of marine science and technology, the central management of research activities, and the common development of services and products. It comprises facilities and resources while it provides open access to research communities (academia, industry) to support the scientific advancements and innovation in their fields. The Hellenic Marine Observing, Forecasting and Technology System was further enhanced during its implementation through significant upgrades and developments in order to extend its observing capacity and the forecasting and technological abilities, while advancing the provided services and products.

One-year assessment of the two-way coupled atmosphere-ocean wave modeling system CHAOS over the Mediterranean and Black Seas - GEORGE VARLAS; CHRISTOS SPYROU; ANASTASIOS PAPADOPOULOS; GERASIMOS KORRES; PETROS KATSAFADOS (Mediterranean Marine Science, 2020)
Nowadays, it has become clear that atmosphere and ocean should be simulated by integrated modeling systems resolving interconnected physical factors which determine Earth’s energy balance. Waves play a key role on the interfacial interaction between atmosphere and ocean regulating momentum, heat and moisture exchange. This study aims to evaluate the two-way coupled atmosphere-ocean wave system CHAOS (Chemical Hydrological Atmosphere Ocean wave System) over the Mediterranean and Black Seas. The evaluation is performed against in-situ and remote sensing data for the period from 1 December 2013 to 1 December 2014. CHAOS includes the Weather Research Forecasting (WRF) model version 3.8 as atmospheric component and the Wave model (WAM) cycle 4.5.4 as ocean wave component, coupled through the OASIS3-MCT coupler version 3.0. In order to assess the impact of the atmosphere-ocean waves coupling, two approaches of continuous model simulations are followed. In the first approach (1-way coupling mode) the ocean wave component uses the winds produced by the atmospheric component while in the second approach (2-way coupling mode) the atmospheric component additionally uses the sea state information estimated by the ocean wave component through wave-dependent Charnock parameter computations. In the 2-way coupling mode, the attenuation of the atmospheric flow has a damping effect on wind-generated waves. The simulations in 2-way coupling mode produce more realistic results yielding statistical improvements. Against buoys observations, 2-way reduces root mean square error (RMSE) per 1.2% and 6.3% for wind speed and significant wave height, respectively, while against Jason-2 satellite retrievals per 0.5% and 2.4%, respectively. Additionally, the 2-way outperforms the 1-way coupling mode under intense wind and wave conditions during this one-year period.

Eta model simulations using two radiation schemes in clear-sky conditions - Diêgo de Andrade Campos; Sin Chan Chou; Christos Spyrou; Júlio Cesar Santos Chagas; Marcus Jorge Bottino (Meteorology and Atmospheric Physics, 2018)

Hare harvest and EBHS virus prevalence in differently populated Mediterranean ecotopes - Christos Sokos; Alexios Giannakopoulos; Konstantinos Papaspyropoulos; Antonia Touloudi; Periklis Birtsas; Vassiliki Spyrou; George Valiakos; Constantina Tsokana; Athanasios Sfougaris; Charalambos Billinis (European Journal of Wildlife Research, 2016)

Conservation Considerations for a Management Measure: An Integrated Approach to Hare Rearing and Release - Christos Sokos; Periklis Birtsas; Konstantinos G. Papaspyropoulos; Alexios Giannakopoulos; Labrini V. Athanasiou; Katerina Manolakou; Vassiliki Spyrou; Charalambos Billinis (Environmental Management, 2015)

Exposure of Eurasian magpies and turtle doves to West Nile virus during a major human outbreak, Greece, 2011 - George Valiakos; Antonia Touloudi; Labrini V. Athanasiou; Alexios Giannakopoulos; Christos Iacovakis; Periklis Birtsas; Vassiliki Spyrou; Zisis Dalabiras; Liljana Petrovska; Charalambos Billinis (European Journal of Wildlife Research, 2012)